Development of Hydrophone Sensor System for Autonomous Underwater Vehicle Application - Mohd Aras, Mohd Shahrieel; Hairi, Mohd Hendra; Jamaluddin, Muhamed Herman (2010)
This project is about developing a hydrophone sensor system for the purpose of autonomous underwater vehicle (AUV) application. AUV is an underwater vehicle which travels underwater. Hydrophone is an underwater microphone which with the help of pressure impulses of acoustic waves converts them into electrical signals which in further are used for communication. It was designed to be used underwater for recording or listening to underwater sound. Hydrophone needs an audio recorder to analyze the spectrographic analysis, without necessary to carry the computer into hostile marine environment. Spectrogram is used to simulate the sound signal of underwater sounds. Spectrogram is a plot of the frequency component such an audio signal as function of time. In this spectrogram program, digital audio recording are analyzed to produce a plot of frequency versus time, with harmonic intensity represented by a variable color scale. Then, the hydrophone system is tested by recording the underwater sound signals at the location to make sure that the system in good condition.